Investigation of the current requirements engineering practices among software developers at the Universiti Utara Malaysia Information Technology (UUMIT) Centre - Hussain, Azham; Mkpojiogu, Emmanuel O. C.; Abdullah, Inam (2016)
Requirements Engineering (RE) is a systemic and integrated process of eliciting, elaborating, negotiating, validating and managing of the requirements of a system in a software development project. UUM has been supported by various systems developed and maintained by the UUM Information Technology (UUMIT) Centre. The aim of this study was to assess the current requirements engineering practices at UUMIT. The main problem that prompted this research is the lack of studies that support software development activities at the UUMIT. The study is geared at helping UUMIT produce quality but time and cost saving software products by implementing cutting edge and state of the art requirements engineering practices. Also, the study contributes to UUM by identifying the activities needed for software development so that the management will be able to allocate budget to provide adequate and precise training for the software developers. Three variables were investigated: Requirement Description, Requirements Development (comprising: Requirements Elicitation, Requirements Analysis and Negotiation, Requirements Validation), and Requirement Management. The results from the study showed that the current practice of requirement engineering in UUMIT is encouraging, but still need further development and improvement because a few RE practices were seldom practiced.